MacArthur’s Air Force American Airpower Over the Pacific and the Far East, 1941–51 - Yenne, Bill
General Douglas MacArthur ended World War II controlling one of the most powerful air forces in the world. This fascinating history, now available in paperback, traces its development from its origins in the Philippines through to its eventual victory in the skies over Japan and its key role in the Korean War.